Combined laryngocele: benign but potentially fatal lesion of the larynx - Ferreira, Joana Maria Soares (2020)
We present a case of a combined laryngocele with the purpose of alerting to the diagnosis and treatment of this laryngeal condition, which, although benign, can be associated with malignant neoplasms and, in rare cases, complicate with airway obstruction, asphyxia and death. We describe the case of a 56-year-old male patient, with a personal history of tobacco abuse, who went to the emergency department with complaints of unilateral cervical swelling and dysphonia, with three months of evolution, and orthopnea. The physical examination revealed a 6 cm wide, cystic and reducible left upper cervical swelling, with a positive cough impulse and an increase in size after the Valsalva maneuver. Nasofibrolaryngoscopy revealed a submucosal swelling in the left ventricular region and aryepiglottic folds. Cervical MRI confirmed the presence of a large combined laryngocele. This lesion was successfully excised with an external cervical surgical approach.